The making of a leader what elite sport can teach us about leadership, management and performance - Young, Tom. (London Robinson, 2020)
Performance psychologist Tom Young has worked closely with teams and individuals at the highest level of professional sport. He has seen how leaders in these high-pressure environments communicate, how they maintain focus and respond to challenges. In The Making of a Leader, Young shares the practical principles of sustained elite performance and shows how any individual can add value to their own business or organisation by applying these insights.
xxiv, 360p. ; 24 cm
Keywords: Leadership